USING MAGIC SENTENCES TECHNIQUE TO IMPROVE STUDENTS’ VOCABULARY - Parmawati, Aseptiana (Lingual Journal of Language and Culture, 2019)
Abstract   In the process of learning a foreign language, vocabulary is one of the important language elements that must be mastered by the learners . The ability to understand the language depends on one’s knowledge of vocabulary besides the other elements of language itself. In reality, most of the students in first semester at IKIP Siliwangi face some problems related to vocabulary mastery. To improve the students’ vocabulary, the lecturer need to know what technique is the most suitable for the students. This research used Classroom Action Research (CAR). The objectives of the study are: 1) Finding out whether or not Magic Sentences technique can improves the students’ vocabulary 2) Finding out classroom situation when Magic Sentences technique implemented in vocabulary mastery. The finding was supported by the result of students’ vocabulary scores. The average score of pre test was 61.14. After the implementation of Magic Sentences in every cycle, the students’ vocabulary score were getting better. It can be seen from the result of students’ average score Cycle 1 was 67.30 and Cycle 2 was 80.24. It can be concluded that Magic Sentences can improve students’ reading interest and improve reading classroom into a better situation.   Keywords: Magic sentences; vocabulary mastery; CAR